Legionella clemsonensis sp. nov.: a green fluorescing Legionella strain from a patient with pneumonia. (October 2016) - Palmer, Allison; Painter, Joseph; Hassler, Hayley; Richards, Vincent P.; Bruce, Terri; Morrison, Shatavia; Brown, Ellen; Kozak‐Muiznieks, Natalia A.; Lucas, Claressa; McNealy, Tamara L.
ABSTRACT: A novel Legionella species was identified based on sequencing, cellular fatty acid analysis, biochemical reactions, and biofilm characterization. Strain D5610 was originally isolated from the bronchial wash of a patient in Ohio, USA. The bacteria were gram‐negative, rod‐shaped, and exhibited green fluorescence under long wave UV light. Phylogenetic analysis and fatty acid composition revealed a distinct separation within the genus. The strain grows between 26–45°C and forms biofilms equivalent to L. pneumophila Philadelphia 1. These characteristics suggest that this isolate is a novel Legionella species, for which the name Legionella clemsonensis sp nov. is proposed.